TECHNOLOGY FOR DEVELOPING READING COMPETENCE OF NON-PHILOLOGICAL UNIVERSITY STUDENTS (ON THE EXAMPLE OF PHYSICS SPECIALIZATIONS) (KONFERENSIYA, 2025)
This article highlights the technology of developing foreign language reading competence among students of non-philological fields, particularly those specializing in physics. Reading competence plays a crucial role in understanding scientific texts, interpreting terminology, working with international academic sources, and fostering independent learning. The article discusses a step-by-step technological approach, reading strategies, and the use of modern information technologies in this process.